2023
DOI: 10.1073/pnas.2221863120
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively active B2 Raf-like kinases are required for drought-responsive gene expression upstream of ABA-activated SnRK2 kinases

Abstract: Osmotic stresses, such as drought and high salinity, adversely affect plant growth and productivity. The phytohormone abscisic acid (ABA) accumulates in response to osmotic stress and enhances stress tolerance in plants by triggering multiple physiological responses through ABA signaling. Subclass III SNF1–related protein kinases 2 (SnRK2s) are key regulators of ABA signaling. Although SnRK2s have long been considered to be self-activated by autophosphorylation after release from PP2C-mediated inhibition, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…There is still no answer to why OST1 loss‐of‐function plants generally show strong stomatal insensitivities to different abiotic stimuli, while there are many alternative kinases (CPK3, CPK6, CPK21, and CPK23) activating SLAC1 and other anion channels present (Merilo et al, 2013). Recently, B2 Raf‐like kinases were found to activate SnRK2s in an ABA‐dependent way under mild drought stress, whereas B3 Raf‐like kinases enhanced SnRK2 activity ABA‐independently under severe drought stress (Soma et al 2023). These regulations could also be involved in the active response of ost1‐3 , either via changes in hydraulic conductance or activation of stress‐induced gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…There is still no answer to why OST1 loss‐of‐function plants generally show strong stomatal insensitivities to different abiotic stimuli, while there are many alternative kinases (CPK3, CPK6, CPK21, and CPK23) activating SLAC1 and other anion channels present (Merilo et al, 2013). Recently, B2 Raf‐like kinases were found to activate SnRK2s in an ABA‐dependent way under mild drought stress, whereas B3 Raf‐like kinases enhanced SnRK2 activity ABA‐independently under severe drought stress (Soma et al 2023). These regulations could also be involved in the active response of ost1‐3 , either via changes in hydraulic conductance or activation of stress‐induced gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the presence of ABA, ABA receptors PYR1/PYLs /RCARs bind ABA to form a complex with PP2Cs and inhibit the activities of these PP2Cs (Ma et al, 2009;Park et al, 2009;Tischer et al, 2017). The released SnRK2s can be phosphorylated and activated by other protein kinases such as Rapidly Accelerated Fibrosarcoma-LIKE MITOGEN-ACTIVATED PROTEIN KINASE KINASE KINASEs (Raf-like MAPKKKs) (Saruhashi et al, 2015;Fàbregas et al, 2020;Lin et al, 2020;Soma et al, 2020Soma et al, , 2023Takahashi et al, 2020; Figure 1). Furthermore, activated-SnRK2s, such as SnRK2.6/OST1, positively regulate the activity of guard cell plasma membrane-localized R-type (QUAC1/ALMT12) and S-type (SLAC1) anion channels, thus closing the stomata (Geiger et al, 2009;Meyer et al, 2010;Sasaki et al, 2010;Imes et al, 2013).…”
Section: Drought Stressmentioning
confidence: 99%
“…These results indicate that additional proteins are required to initiate SnRK2.6/OST1 activity in planta. Recently, with a combination of forward genetic screen and phosphoproteomics approaches, several independent groups have reported and identified that MAPKKK-RAFs play an essential role in the activation of SnRK2s in Arabidopsis (Nguyen et al, 2019;Katsuta et al, 2020;Lin et al, 2020;Soma et al, 2020Soma et al, , 2023Takahashi et al, 2020;Lin et al, 2021;Wang et al, 2023a; Figure 1). Arabidopsis SnRK2s can be quickly activated in response to osmotic stress, which is independent of the ABA signaling pathway (Boudsocq et al, 2004(Boudsocq et al, , 2007Yoshida et al, 2002Yoshida et al, , 2006.…”
Section: Drought Stressmentioning
confidence: 99%
See 2 more Smart Citations